Studi Komparatif Larangan Perkawinan Antara Hukum Adat, Hukum Perdata dan Hukum Islam - Djun’astuti, Erni; Tahir, Muhammad; Marnita, Marnita (Fakultas Syariah INSURI Ponorogo, 2022)
This study aims to thoroughly implement the Prohibition of Marriage from the Perspective of Customary Law, Civil Law, and Islamic Law. Second, describe the application of sanctions for violations of marriage prohibitions according to customary law, civil law, and Islamic law. Third, analyze prevention efforts to avoid infringements of the Prohibition of Marriage. The research method used is a qualitative research type, with a descriptive-analytic way applying a literature and literature study approach accompanied by observations on applications that occur in the community. Currently, in Indonesia, it can be seen in the community many cases of marriage that occur without regard to the Prohibition of Marriage. As a legal state that adheres to several national legal systems, it is expected to guarantee legal certainty for all its citizens. Therefore, there is a need for synergy between all applicable policies in Indonesia on the Prohibition of Marriage